2009
DOI: 10.1007/s11069-009-9452-6
|View full text |Cite
|
Sign up to set email alerts
|

Flood risk curves and uncertainty bounds

Abstract: Although flood risk assessments are frequently associated with significant uncertainty, formal uncertainty analyses are the exception rather than the rule. We propose to separate two fundamentally different types of uncertainty in flood risk analyses: aleatory and epistemic uncertainty. Aleatory uncertainty refers to quantities that are inherently variable in time, space or populations of individuals or objects. Epistemic uncertainty results from incomplete knowledge and is related to our inability to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
193
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(198 citation statements)
references
References 36 publications
2
193
0
3
Order By: Relevance
“…The model is applicable on the microscale, i.e., on the object level, as well as on the mesoscale, i.e., on homogeneous land use units. For both scales it was successfully validated ) and applied or modified in different studies (e.g., Kreibich and Thieken, 2008;Apel et al, 2009;Merz and Thieken, 2009;Wuensch et al, 2009;Elmer et al, 2010;Kreibich et al, 2011b;Merz et al, 2013).…”
Section: Derivation Of the Flood Loss Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The model is applicable on the microscale, i.e., on the object level, as well as on the mesoscale, i.e., on homogeneous land use units. For both scales it was successfully validated ) and applied or modified in different studies (e.g., Kreibich and Thieken, 2008;Apel et al, 2009;Merz and Thieken, 2009;Wuensch et al, 2009;Elmer et al, 2010;Kreibich et al, 2011b;Merz et al, 2013).…”
Section: Derivation Of the Flood Loss Modelsmentioning
confidence: 99%
“…Even if the full range of the underlying asset values (i.e., the minimum (EUR 224 per m 2 ) and maximum (EUR 353 per m 2 ) values) is applied, none of these two functions is within the confidence interval in one of the two hydraulic-simulation runs. Some of these three standard functions were already used in different geographical regions before like in the German federal states of Saxony (Schwarz et al, 2005;Thieken et al, 2008) and Baden-WĂŒrttemberg Apel et al, 2009;Merz and Thieken, 2009) but it has also been reported that these models tend to under-or overestimate observed damage to buildings (e.g., Schwarz et al, 2005;Thieken et al, 2008;Apel et al, 2009).…”
Section: Comparison Of the Modeled Flood Damage With The Observed Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies that quantify flood hazard and expected changes in the hazard due to sea-level rise (Nicholls and Cazenave, 2010). Other studies use flood risk assessment models, focusing both on the flood hazard, and on flood exposure and vulnerability (Apel et al, 2008;Merz and Thieken, 2009;Ward et al, 2011a). Some of these studies use catastrophe risk models to calculate risk reduction for different flood adaptation measures on local to regional scales (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There exist many different methodologies to derive flood losses (Merz and Thieken, 2009;Apel et al, 2009a), typically in the suite: discharge (stage) -damage, or discharge -return period -damage, developed for a range of scalesfrom local to national or continental. However, the issue of Cammerer et al (2013) examined adaptability and transferability of stage-damage functions for the estimation of direct flood damage to buildings.…”
Section: The Damage Functions D (T ) and The Flood Loss Model Hq Kumumentioning
confidence: 99%